El dibujo y la simbolización en algunos casos de maltrato infantil. // Drawing and symbolization in some cases of child maltreatment. A psychoanalytical look - Nicolás Uribe Aramburo. (Affectio Societatis, 2009)
This article makes part of a research carried out within the framework of the Master in Psychoanalytical Research, which comes up from the analysis of clinical material obtained from psychotherapeutic work developed during more than three years with children coming to a psychology service of a non-profit institution located in one of Medellin's communes, mainly because of problems related to child maltreatment. In order to obtain such analysis material, we started from the psychoanalytical thesis of psychic determinism and the neutrality of the therapist. For that reason we invited some kids to draw and associate freely, expecting what they showed would be related to their maltreatment experiences. Consequently, the methodology used consisted not only in handing over to children but in leading them to use drawing. // Este artículo es parte de una investigación llevada a cabo en el marco de la Maestría en Investigación psicoanalítica, que surge del análisis del material clínico obtenido en el trabajo psicoterapéutico realizado por más de tres años con población infantil que acudía a un servicio de psicología de una institución sin ánimo de lucro ubicada en una de las comunas de la ciudad de Medellín, principalmente por problemáticas asociadas al maltrato infantil. Para obtener dicho material de análisis partimos de las tesis psicoanalíticas del determinismo psíquico y la neutralidad del terapeuta, razón por la cual invitamos a los niños a dibujar y asociar libremente con la expectativa que de que aquello que exteriorizaran tendría una relación con sus vivencias de maltrato. En consecuencia, la metodología utilizada no sólo consistió en darles la palabra a los niños, sino que también implicó inducirlos a usar el dibujo.